2016
DOI: 10.1111/1742-6723.12704
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of first‐pass success rates in emergency department intubation: Creating a benchmark for emergency airway care

Abstract: Research published in the last 16 years shows a mean ED FPS rate of 84.1%. This represents the best available published data that can be used to benchmark emergency airway performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
83
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 32 publications
(58 reference statements)
6
83
0
1
Order By: Relevance
“…The majority of patients were men, and most had a medical indication for intubation, similar to other studies. 23 We found that ED intubation is not generally challenging because of anatomical difficulty (the majority were CL grade I or II) but likely due to a patient's physiological derangements, disease process and situational urgency. Although a pre-intubation checklist did not favourably influence success or complication rates, we support its use due to the potential to reduce stress and error during this high-risk procedure.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The majority of patients were men, and most had a medical indication for intubation, similar to other studies. 23 We found that ED intubation is not generally challenging because of anatomical difficulty (the majority were CL grade I or II) but likely due to a patient's physiological derangements, disease process and situational urgency. Although a pre-intubation checklist did not favourably influence success or complication rates, we support its use due to the potential to reduce stress and error during this high-risk procedure.…”
Section: Discussionmentioning
confidence: 75%
“…13,21,22 A reduced first attempt success for trauma patients has also been previously reported. 23 We found that ED intubation is not generally challenging because of anatomical difficulty (the majority were CL grade I or II) but likely due to a patient's physiological derangements, disease process and situational urgency. The complication rate of 26.0% is higher than reported elsewhere.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Repeated or prolonged intubation attempts exhaust any physiologic reserve these patients may have, leading to more frequent adverse outcomes (6). Thus, maximizing first attempt success without an adverse event is the goal for airway management in this high-risk population (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…For 3710 episodes of intubation over 2 years in 38 EDs, there was an intubation rate of approximately 1:500 ED presentations. In a recent meta‐analysis of 16 ED airway papers describing 42 081 episodes of intubation, the cricothyrotomy rate was 0.3%, and the peri‐intubation cardiac arrest rate was 0.6%. Therefore, for any individual ED to identify systems issues from patterns in these very rare, yet potentially catastrophic presentations, would take an unconscionable period of time.…”
Section: Introductionmentioning
confidence: 99%